Exploring teacher leadership: A case study at a senior secondary school in the Ohangwena region, Namibia - Hamatwi, Isak (Rhodes University, Faculty of Education, Department of Education, 2016)
Leadership has been for long thought to centre on the actions of a positional head of the organisation crafting the vision and influencing followers' behaviour based on his/her charisma and legal authority in a quest to achieve the set goals (Christie, 2010). However, contemporary views "emphasise leadership as relational" (Van der Mescht & Tyala, 2008, p. 226) and focuses more on the practice while taking form "in the interactions between leaders and followers" (Spillane, 2005, p. 146). Looking through the lens of distributed leadership and using the Grant's (2008; 2012) model of teacher leadership as a data analytical tool, this research study aimed to explore the enactment of teacher leadership at a secondary school in the Ohangwena region, Namibia. The motivation of this research study was twofold; one, it was due to my personal interest in getting a deeper understanding of what constituted teacher leadership as a concept which is gaining momentum in the educational leadership discipline; two, it was due to the evident knowledge gap existing on the concept of teacher leadership as there seemed to be very less research done on the concept. Using observation schedules, survey questionnaires, semi-structured interview schedules and analysing documents as data collecting tools, the study was geared towards answering four research questions which were driving the study, namely; i) In what ways do teachers participate in the leadership activities of the school? ii) What is the nature of the relations of these leadership activities? iii) What factors that may constrain the leadership activities of these teachers? iv) How do the principal and the School Management Team (SMT) encourage teacher leadership at the school? The study was of a qualitative nature located in the interpretive paradigm. A purposive sampling method was used to select research participants The findings of the study indicated that the research participants had a general understanding of what teacher leadership entails. Teachers enacted leadership across the four zones of Grant's (2008; 2012) model of teacher leadership, though with very limited teacher leadership enactment in zone four. Zones one, two and three proved to be the popular media of teacher leadership enactment wherein teachers led in their classrooms enforcing discipline, serving as guides and caregivers to their learners (zone one). Teachers then extended their leadership outside their classrooms where they served as decision makers, curriculum developers for knowledge enhancement through reflective teaching and sport coaches (zone two). In Zone three, teachers led in committees' structures, as mentors of learners, policy makers and as models of good practice. Zone four was the least media of teacher leadership. The data pointed to a host of factors that prevented teachers to assume leadership at the case study school, namely; ignorance and fear for accountability, policy and regulatory limitations, time limitations, limited skills and teachers as barriers to teacher leadership in terms of apathy, lack of confidence, negative attitude and anti-social behaviours as well as professional jealous. Nevertheless, the principal and the SMT emerged as catalysts for teacher leadership at the school as they enabled teacher leadership in a number of ways, namely, through delegation, motivation, free choice, open engagement, moral support and interdependence leadership practices. In the final analysis, the findings revealed that, leadership at the case study school was manifested as spontaneous collaborated leadership practices through institutionalised practices embarked upon with intuitive working relationships.
Keywords: Uncatalogued